The wooing of Earth - Dubos, René J. (René Jules) 1901-1982 (Charles Scribner's Sons, 1980)
Examines man's relationship to nature from an historical and biological perspective, discusses the destruction of many of the world's ecosystems, and suggests methods for reversing damage that has been done to the natural world